MODERASI STRUKTUR MODAL DALAM MEMENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR PERTANIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2023 - Rofiqi, Muhammad; Tulhusnah, Lusiana; Subaida, Ida (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
In the business world, companies must pay attention not only to profitability but also to liquidity, as both significantly influence the company's survival and growth. One strategic sector in the Indonesian economy is the agricultural sector, which plays a vital role in supporting the national economy. Nevertheless, the agricultural sector operates in an environment fraught with challenges, such as climate change, commodity price uncertainty, and regulatory changes that can affect company performance. During the 2020-2023 period, 30 agricultural sector companies were listed on the Indonesia Stock Exchange. The performance of these companies underwent various changes, including the impact of the COVID-19 pandemic. Therefore, companies must have effective financial strategies to ensure business continuity and enhance company value. The purpose of this research is to analyze and test the moderation of capital structure on the influence of liquidity and profitability on company value. The population in this study consists of 30 agricultural sector companies listed during the research period on the Indonesia Stock Exchange. The sampling technique employed was purposive sampling. Data analysis and hypothesis testing were conducted using Structural Equation Modeling – Partial Least Square (PLS-SEM). The results of the hypothesis testing using the Smart PLS 3.0 application showed that liquidity has a positive but insignificant effect on company value, profitability has a positive but insignificant effect on company value, capital structure does not significantly moderate the influence of liquidity on company value, and capital structure does not significantly moderate the influence of profitability on company value.